GENDER APPROACH IN TEACHING A FOREIGN LANGUAGE (World Bulletin of Social Sciences, 2021)
In the modern world, the problem of gender education is of concern to both scientists and practitioners. This is largely due to the fact that attention to the child is increasing, and gender characteristics are one of the main characteristics of the personality. Namely, upbringing presupposes the correct assimilation of gender roles, which implies gender equality, the absence of gender prejudices and gender discrimination. The need to use a gender approach in teaching and upbringing of schoolchildren and young learners is noted by many domestic and foreign teachers